2018
DOI: 10.1186/s12938-018-0600-7
|View full text |Cite
|
Sign up to set email alerts
|

Objective and automatic classification of Parkinson disease with Leap Motion controller

Abstract: BackgroundThe main objective of this paper is to develop and test the ability of the Leap Motion controller (LMC) to assess the motor dysfunction in patients with Parkinson disease (PwPD) based on the MDS-UPDRSIII exercises. Four exercises (thumb forefinger tapping, hand opening/closing, pronation/supination, postural tremor) were used to evaluate the characteristics described in MDS-UPDRSIII. Clinical ratings according to the MDS/UPDRS-section III items were used as target. For that purpose, 16 participants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(76 citation statements)
references
References 38 publications
3
64
0
2
Order By: Relevance
“…Indeed, the set of spatiotemporal features that obtained the maximum accuracy included parameters extracted from Gait, Heel-Toe Tapping, Pronation/Supination, Finger Tapping, Arms Swing, and Postural Tremor, confirming the significance of these exercises already found in previous works 4 , 5 for the assessment of motor dysfunction in patients with PD. Furthermore, the selected features are derived from accelerometers and gyroscopes, suggesting that both sensors are equally important for capturing clinically relevant information.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Indeed, the set of spatiotemporal features that obtained the maximum accuracy included parameters extracted from Gait, Heel-Toe Tapping, Pronation/Supination, Finger Tapping, Arms Swing, and Postural Tremor, confirming the significance of these exercises already found in previous works 4 , 5 for the assessment of motor dysfunction in patients with PD. Furthermore, the selected features are derived from accelerometers and gyroscopes, suggesting that both sensors are equally important for capturing clinically relevant information.…”
Section: Discussionsupporting
confidence: 82%
“…The chosen feature selection methods have been used in previous studies to obtain the optimum set of parameters to increase the overall accuracy of the system. 4 , 15 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results demonstrated the ability of supervised classification methods with a relatively high accuracy. An automatic SVM based study with leap motion controller recruited 16 PD and 12 HCs, and the accuracy was 74.07% with an AUC of 0.675 (Butt et al, 2018). Another study of SPECT imaging using SVM and logistic regression (LR) showed that SVM method produced a higher accuracy of 85% than LR of 83%, and the authors claimed that the SVM-based model could provide better guide for PD stage classification (Hsu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Hand gesture recognition is widely researched as it can be applied to different areas such as human-computer interaction [1], robotics [2], computer games [3], education [4], automatic sign-language interpretation [5], decision support for medical diagnosis of motor skills disorders [6], recognition of children with autism [7], home-based rehabilitation [8,9], virtual training [10] and virtual surgery [11]. In industry, gesture recognition can be used in areas requiring very high precision such as to control devices such as robot hands [12] or industrial equipment.…”
Section: Introductionmentioning
confidence: 99%